1992
DOI: 10.1093/ageing/21.6.435
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Vitamin A Supplementation on the Incidence of Infection in Elderly Nursing-home Residents: A Randomized Controlled Trial

Abstract: The aim of this study was to determine if vitamin A supplementation reduces the incidence of bacterial infections among elderly nursing-home residents. One hundred and nine patients were enrolled into a double-masked, placebo-controlled trial at an academically affiliated nursing home. Fifty-six patients received a single capsule containing 1,000 IU of vitamin A (placebo) and 53 received a single capsule containing 200,000 IU of vitamin A. Antibiotic-treated infections were enumerated for 90 days after dosing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

1998
1998
2014
2014

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(12 citation statements)
references
References 0 publications
1
11
0
Order By: Relevance
“…Thirtyseven publications were excluded for the following reasons: subjects not residents of nursing home (n = 8), publication not a research publication (n = 1), and trial occurred outside the United States (n = 28). The 45 publications in the final sample came from 21 journals 12–56 . These publications reported the following kinds of research: drug intervention 27% (12/45), care intervention 22% (10/45), device intervention 16% (7/45), physical or occupational therapy intervention 13% (6/45), assessment instrument 11% (5/45), patient or staff education 4% (2/45), behavior intervention 2% (1/45), diet intervention 2% (1/45), and electrolyte measurement 2% (1/45).…”
Section: Resultsmentioning
confidence: 99%
“…Thirtyseven publications were excluded for the following reasons: subjects not residents of nursing home (n = 8), publication not a research publication (n = 1), and trial occurred outside the United States (n = 28). The 45 publications in the final sample came from 21 journals 12–56 . These publications reported the following kinds of research: drug intervention 27% (12/45), care intervention 22% (10/45), device intervention 16% (7/45), physical or occupational therapy intervention 13% (6/45), assessment instrument 11% (5/45), patient or staff education 4% (2/45), behavior intervention 2% (1/45), diet intervention 2% (1/45), and electrolyte measurement 2% (1/45).…”
Section: Resultsmentioning
confidence: 99%
“…A study conducted by Murphy et al 29 showed no effect on the rates of infection in an older group given supplements of vitamin A. Therefore, it may be possible that vitamin A supplementation will benefit only vitamin A‐deficient children 26 …”
Section: Discussionmentioning
confidence: 99%
“…Clinical trials in LTCFs have reported no decrease in infections with routine vitamin or mineral supplementation. 225,226 However, optimal care of comorbid illnesses and good nutrition are principles of care irrespective of impact on infections.…”
Section: Resident Healthmentioning
confidence: 99%